Pelaksanaan Pertanggungjawaban Sosial Perbankan terhadap Koperasi dalam Hal Sertifikasi Kekayaan Intelektual Sebagai Jaminan Kredit Perbankan - Wibi Anska Putri (Wajah Hukum, 2020)
HKI is a work declared by creative economic actors as an effort to encourage Indonesia's economic growth. In addition to being a form of legal protection, the existence of one type of HKI namely the brand can be used as a concept as collateral. In fact, there is no legal force to implement this because there are no regulations governing it, causing legal uncertainty for the parties involved, especially regarding the policy of banking institutions in providing credit to cooperatives or UMKM that have been certified. The results of this paper show that the application of collective brand certificates to be used as collateral for bank loans does not yet have legal certainty, and the efforts that can be made by the government are to harmonize regulations, provide counseling on the importance of the existence of HKI, and monitor the balance between applicable rules and reality. which took place in the field. The role of cooperatives or UMKM is to maintain good performance when banking institutions have provided access to capital in the form of credit by implementing the Linkage Program Executing pattern based on the principle of consensus or trust and applying risk management principles in each credit agreement. The social responsibility of banking institutions in this case is to provide easing of collateral and is not commercial in nature.